Cu+-containing physically crosslinked chitosan hydrogels with shape memory - Z. Y. Yu; Y. Li; Z. P. Feng; Z. H. Zhang; P. Li; Y. Chen; S. S. Chen; P. W. Li; Z. M. Yang (eXPRESS Polymer Letters, 2019)
Physically crosslinked chitosan hydrogels have better biocompatibility and possess unique functional characteristics but suffer from poor mechanical properties. In the current study, we prepared Cu+-containing physically crosslinked chitosan hydrogels by exploiting ammonia fumigation and reduction of Cu2+ by NaHSO3. The content of Cu+ in the prepared hydrogels was in a low range of 4.88–29.27 μmol/g. The mechanical strength of the CTS-Cu+/NH3 hydrogels was remarkably improved up to 0.25 MPa and the elongation at break increased with rising content of Cu+ due to the dynamic crosslinks between chitosan and Cu+. Moreover, the CTS-Cu+/NH3 hydrogels demonstrated evident shape memory after exposure to air by exploiting the different coordination number of Cu2+ and Cu+. Thus, the prepared hydrogels may have good potential applications as biomedical materials.